TEMBANG “LIR-ILIR” BAGI GURU GUNA MENUMBUHKAN MOTIVASI BELAJAR DI PENDIDIKAN FORMAL (STUDI KASUS DI TK WAHID HASYIM DINOYO MALANG) - Pujiharti, Endang Sih (J-MPI (Jurnal Manajemen Pendidikan Islam), 2016)
Motivation to learn in early childhood are things that need attention from parents, teachers and the community, because it is generally a child is still not able to realize the wishes and needs related to learning without the help of others. Song "Lir-ilir" by Sunan Kalijaga, has a very important significance and depth that can be used as a source of inspiration by teachers to motivate children's learning, because teachers are the leaders for the students. This study aims to determine: 1) The meaning implied in the song "Lir-ilir"; 2) The role of teachers in schools with regard to early childhood learning motivation; 3) Efforts that teachers do to motivate learning early childhood by making the meaning of the song "Lir-ilir" as a source of inspiration. This study used a qualitative approach and descriptive method. The data was collected through interviews, observation and documentation. Result: 1 ) meaning contained in the song "Lir-ilir" very important and in-depth, 2) one of the teacher's role is very important in the learning process is as a motivator. Then the teacher demanded to motivate children's learning. 3) efforts undertaken teachers to motivate the child to learn to make meaning of the song "Lir-ilir" as a source of inspiration is: learn singing, learning through play, using props and iridescence of interest in learning.